Investigating the Use Profile of Kigelia africana (Lam.) Benth. through Market Survey in Benin - Dossou-Yovo, Hubert Olivier; Vodouhê, Fifanou G.; Valentin Kindomihou, Valentin Missiakô; SINSIN, AUGUSTIN BRICE (My University, 2022)
This research focuses on Kigelia africana in Benin where it is widely used in traditional medicine but receives little attention from researchers. In addition, this species has recently been recorded as threatened in the country. The aim was to gather ethnobotanical knowledge using a printed semi-structured questionnaire to collect data from herbal medicine traders, randomly selected, through a face-to-face discussion. The survey was carried out from January to March 2020. Among 36 questioned herbal traders, 36% of respondents obtained parts of K. africana by purchase in their own markets and by travelling far (3–10 km covered). The same proportion travel very far before buying parts (more than 10 km covered). None mentioned harvesting parts from wild populations. A high proportion of informants (63%) sold fruits and stem bark whereas a relatively low proportion of them (37%) sold fruits, stem bark, and leaves. The stem bark was recorded as most in demand followed by fruits. Respondents mostly confirmed the species scarcity. This species was used to treat 13 diseases and disorders. The stem bark was the most cited in the management of stomach infections and gynecological disorders. Fruits were mainly used in magic rituals and the treatment of stomach infections. Five preparations were recorded whither 54% of traders mentioned bark decoctions and 27% highlighted infusion of fruits in water. Overall, Kigelia africana is an important plant in Beninese ethnomedicine and the harvest and trade of its different parts represent major threats. Therefore, urgent conservation tools and actions are needed.
Keywords: Kigelia africana; ethnobotanical knowledge; Benin; herbal medicine traders; infections